(untitled) (Herald of the National Children’s Medical Center, 2022)
Protecting and strengthening the health of the nation – including mass public health campaigns have a direct link in obtaining the desired effect in reducing the frequency and burden of morbidity, which is mostly directly related to changing people’s behavior. It is quite difMcult to achieve this, but it is possible through its prerequisites: raising awareness not only about diseases, but also ways to prevent them, disseminate knowledge and change psychological attitudes.